2022
DOI: 10.1029/2022jd037730
|View full text |Cite
|
Sign up to set email alerts
|

Southern Hemisphere Response to the Secondary Planetary Waves Generated During the Arctic Sudden Stratospheric Final Warmings: Influence of the Quasi‐Biennial Oscillation

Abstract: Based on the Modern‐Era Retrospective analysis for Research and Applications version 2 reanalysis and Aura Microwave Limb Sounder geopotential height observations, the anomalously strong secondary planetary waves (PWs) with westward zonal wavenumber 1 and periods of 10–16 days are unexpectedly captured in the Southern (summer) Hemisphere (SH) during the Arctic sudden stratospheric final warmings (SSFWs) in 2015 and 2022, while no distinct secondary PW signal occurs in the SH during the 2005, 2014, and 2016 Arc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 65 publications
(125 reference statements)
0
1
0
Order By: Relevance
“…In this paper, the Aura/MLS GPH data are utilized to study the Q6DW‐W1 activities during the Antarctic SMW events in 2013 and 2014. Previous studies have demonstrated that the Aura/MLS GPH measurements are reliable and suitable for the research of PW activities during stratospheric warming events due to the stable coverage on the polar region (Qin, Gu, Dou, et al., 2021; Qin, Gu, Dou, Teng, et al., 2022; Yamazaki et al., 2021; Yamazaki & Matthias, 2019).…”
Section: Datamentioning
confidence: 99%
“…In this paper, the Aura/MLS GPH data are utilized to study the Q6DW‐W1 activities during the Antarctic SMW events in 2013 and 2014. Previous studies have demonstrated that the Aura/MLS GPH measurements are reliable and suitable for the research of PW activities during stratospheric warming events due to the stable coverage on the polar region (Qin, Gu, Dou, et al., 2021; Qin, Gu, Dou, Teng, et al., 2022; Yamazaki et al., 2021; Yamazaki & Matthias, 2019).…”
Section: Datamentioning
confidence: 99%